UV viscosity-reducing adhesive, UV viscosity-reducing adhesive composition, adhesive tape and preparation method

By using multifunctional acrylate copolymer in UV adhesives for chemical grafting reaction, the existing UV adhesives with complex formulation, poor compatibility and residual glue after UV lighting are solved, and efficient and stable UV light viscosity reduction effect is achieved.

CN119505764APending Publication Date: 2025-02-25CROWN NEW MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411841718.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing UV viscosity reducing glue has a variety of formula compositions, resulting in poor system compatibility and poor performance, and residual glue problems after UV lighting, and the UV light viscosity reducing effect needs to be improved.

Method used

The multifunctional acrylate copolymer is used as the UV adhesive reducing adhesive, and the UV active substance and the acrylate main glue are chemically grafted through chemical grafting reaction to form a UV adhesive with a multifunctional acrylate group, simplifying the formulation composition and improving compatibility.

Benefits of technology

It is achieved without additional UV active monomers or oligomers, which enhance the viscosity reduction effect of UV light, improve the viscosity reduction efficiency, promote the compatibility of various components in the UV adhesive material, ensure stable performance, and no residual glue after UV light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188118240000081
    Figure BDA0005188118240000081
  • Figure BDA0005188118240000101
    Figure BDA0005188118240000101
  • Figure BDA0005188118240000111
    Figure BDA0005188118240000111
Patent Text Reader

Abstract

The invention relates to a UV viscosity-reducing adhesive, a UV viscosity-reducing adhesive composition, an adhesive tape and a preparation method. The UV viscosity-reducing adhesive comprises an acrylate copolymer, wherein the acrylate copolymer comprises a main chain and a multifunctional acrylate side group grafted on the main chain; the main chain is formed by copolymerizing a plurality of polymeric monomers including an acrylate soft monomer, an acrylate hard monomer and a functional acrylate monomer; the acrylate soft monomer is acrylate long-chain alkyl ester, and the carbon atom number of the long-chain alkyl ester is greater than or equal to 4; the acrylate hard monomer is methyl (methyl) acrylate; the functional acrylate monomer is acrylic acid (ester) containing carboxyl and acrylic ester containing hydroxyl; the polyfunctional group acrylate side group is formed by a UV active substance, each molecule of which contains a plurality of acrylate groups and contains one epoxy group, through a reaction between the epoxy group and the carboxyl group on the main chain. The UV viscosity-reducing adhesive has a UV viscosity-reducing function, does not need to additionally add UV active monomers or low polymers, can enhance the UV light viscosity-reducing effect and improve the viscosity-reducing efficiency, and is also beneficial to reducing the ingredient composition of a UV adhesive material and simplifying the preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a UV viscosity-reducing adhesive, a UV viscosity-reducing adhesive composition, an adhesive tape and a preparation method thereof. Background Art

[0002] UV adhesive tape is a type of adhesive material that exhibits high adhesion and initial adhesion when used normally at room temperature, but rapidly decreases in adhesion after a short period of ultraviolet (UV) exposure until it loses pressure sensitivity. The original and most widely used field of UV adhesive is the semiconductor industry, involving the material preparation and transportation process of semiconductor chips, transistors, integrated circuits, etc.; before UV irradiation, it uses its own pressure-sensitive adhesive, fixes and protects the processed materials, and after the preparation process is completed, UV irradiation is used to debond the materials and remove the protection, thus changing the subsequent processing process. In addition to the semiconductor industry, UV adhesive also plays an important role in the preparation and recycling of optical devices. The preparation, fixation, protection and transportation of precision optical components require adhesive adhesive to exert its adhesive properties, and in the subsequent further processing or recycling process, adhesive adhesive is required to exert its adhesive reduction function. In summary, adhesive adhesive is of great significance in high-end manufacturing and high-value material recycling.

[0003] The process of bonding and viscosity reduction involves the relative size of the cohesive force and interfacial force of the adhesive material itself. In principle, the existing viscosity reduction adhesives can be divided into two directions: increasing the cohesive force and reducing the interfacial force: by increasing the cohesive force of the adhesive, the modulus of the adhesive increases rapidly and the material loses its pressure sensitivity, thereby achieving the purpose of viscosity reduction; by reducing the interfacial force, the adhesive is separated from the adherend, thereby achieving the purpose of viscosity reduction. The former method is to introduce epoxy, multifunctional acrylate monomers or resins to promote the chemical crosslinking of the adhesive through light and heat; the latter method is to introduce microspheres and electrolyte salts to destroy the interfacial bonding through heat, electricity, external water infiltration, etc. UV viscosity reduction is a non-contact, easy to control, safe and simple method, which has advantages among all viscosity reduction methods.

[0004] At present, the shortcomings of some UV viscosity-reducing adhesives are mainly manifested in the fact that the diversity of components is not conducive to the compatibility of the system. The main components of the formula of UV viscosity-reducing adhesives on the market are acrylate adhesive body, photoactive monomers or oligomers, thermal curing agents, photoinitiators and solvents. The most important of these are the acrylate adhesive body and the photoactive monomers or photoactive oligomers. The acrylate adhesive body provides bonding properties, while the monomers or oligomers with photoinitiator activity increase the degree of chemical cross-linking of the tape through UV light initiation, thereby reducing viscosity. However, this "two-component" method, or even the addition of additional agents such as silicone additives, may lead to poor system compatibility, which in turn makes the UV viscosity-reducing adhesive prepared by this method have poor performance and residual adhesive after UV irradiation. For example, the preparation of UV viscosity-reducing adhesive in patent CN113897168B uses a variety of additives, which has a potential risk of residual adhesive; the UV viscosity-reducing adhesive prepared in patent CN118496783A even needs to add 0.001-3 parts of surfactant to promote compatibility in order to increase the compatibility of active monomers and resins; and patent CN115232578B uses a mixture of two acrylic resins containing carbon-carbon double bonds with the same chemical composition but different molecular weights of high and low to maintain compatibility.

[0005] Another technical deficiency is that the UV light viscosity reduction effect of the prepared UV light viscosity reduction tape needs to be improved. In principle, the effect of UV light viscosity reduction depends on the content of UV active substances (generally small molecules or oligomers containing acrylates or methacrylates) in the tape and their aggregation mode in the tape material (for example, physical blending or chemical grafting with the main components of the tape). In patent CN115746757A, glycidyl methacrylate is introduced to achieve UV light viscosity reduction; however, the introduction efficiency of this method is low, and on average only one methacrylate group can be introduced per reaction, and 5-30 parts need to be added to achieve a certain viscosity reduction effect (peel strength after UV light exposure>0.2N / 25mm). Although patent CN116262873A uses UV viscosity reduction oligomers with multi-acrylate functionality, the subsequent preparation of UV light viscosity reduction adhesive adopts the method of blending UV viscosity reduction oligomers with acrylate main adhesives; this method may cause phase separation problems between the two, thereby affecting the long-term performance stability of UV viscosity reduction adhesives.

[0006] Finally, the reactions and reaction steps used to prepare multifunctional UV active substances with optical viscosity reduction are often too complicated, resulting in increased costs. The polyurethane-based UV viscosity-reducing adhesive based on dimer acid prepared in patent CN118652657A has a certain degree of complexity in the process of preparing viscosity-reducing active polyurethane oligomers.

[0007] Therefore, preparing a UV viscosity-reducing adhesive with a simple structure, multiple acrylate functionalities, and chemically grafted with an acrylate main adhesive is of great significance for reducing the formulation composition, streamlining the preparation process, and improving the performance of the UV viscosity-reducing adhesive. Summary of the invention

[0008] In view of the shortcomings of the prior art, the first purpose of the present invention is to provide a UV viscosity-reducing adhesive, which itself has a UV viscosity-reducing function and does not require the additional addition of UV active monomers or oligomers. It can enhance the UV light viscosity-reducing effect and improve the viscosity-reducing efficiency, and is also beneficial to promote the compatibility of the components in the UV adhesive material and achieve performance stability.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned UV viscosity-reducing adhesive.

[0010] The third object of the present invention is to provide a UV viscosity-reducing adhesive composition, which has a small formula composition, a simple preparation process, and improves the performance of the UV viscosity-reducing adhesive.

[0011] The fourth object of the present invention is to provide a UV adhesive tape, which has high peeling strength and good fixation before UV irradiation; after UV irradiation, the peeling strength is greatly reduced, and there is no residual adhesive when peeling.

[0012] A fifth object of the present invention is to provide a method for preparing the above-mentioned UV anti-viscosity tape.

[0013] To achieve the first object of the present invention, the present invention provides a UV viscosity-reducing adhesive, which includes an acrylate copolymer, the acrylate copolymer includes a main chain and multifunctional acrylate side groups grafted on the main chain; the main chain is formed by copolymerization of multiple polymerized monomers including acrylate soft monomers, acrylate hard monomers and functional acrylate monomers; the acrylate soft monomer is a long-chain alkyl acrylate, and the number of carbon atoms of the long-chain alkyl is greater than or equal to 4; the acrylate hard monomer is methyl (meth)acrylate; the functional acrylate monomer is a carboxyl-containing acrylic acid (ester) and a hydroxyl-containing acrylate; the multifunctional acrylate side groups are formed by a UV-active substance containing multiple acrylate groups and one epoxy group in each molecule through the reaction of the epoxy group with the carboxyl group on the main chain.

[0014] In some embodiments of the present invention, the UV active material is N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine, wherein three epoxy groups in each molecule react with acrylic acid to form a product having three acrylate groups.

[0015] In some embodiments of the present invention, the mass ratio of acrylate soft monomer, acrylate hard monomer and functional acrylate monomer is (70-90): (10-30): (5-15); preferably, the mass ratio of acrylate soft monomer, acrylate hard monomer and functional acrylate monomer is (70-80): (20-30): (8-12).

[0016] In some embodiments of the present invention, the mass ratio of carboxyl-containing acrylic acid (ester) to hydroxyl-containing acrylic acid ester is 1: (0.2-1); preferably, the mass ratio of carboxyl-containing acrylic acid (ester) to hydroxyl-containing acrylic acid ester is 1: (0.2-0.5).

[0017] In some embodiments of the present invention, the mass ratio of the UV active substance to the total mass of the plurality of polymerizable monomers is (2-5):(20-40); preferably, the mass ratio of the UV active substance to the total mass of the plurality of polymerizable monomers is (2-5):(30-40).

[0018] In some embodiments of the present invention, the acrylate soft monomer is at least one of isooctyl acrylate, n-butyl acrylate, and n-hexyl acrylate; the acrylate hard monomer is at least one of methyl methacrylate and methyl acrylate; the carboxyl-containing acrylic acid (ester) is acrylic acid; and the hydroxyl-containing acrylate is at least one of hydroxyethyl acrylate and hydroxybutyl acrylate.

[0019] In some embodiments of the present invention, the UV viscosity-reducing adhesive further includes a solvent, the mass proportion of the acrylate copolymer in the total mass of the acrylate copolymer and the solvent is 30% to 50%, and the solvent is at least one of ethyl acetate and toluene.

[0020] To achieve the second object of the present invention, the present invention provides a method for preparing a UV viscosity-reducing adhesive according to any of the above schemes, comprising the following steps:

[0021] Step 1: mixing N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine, acrylic acid, a first organic tin catalyst, a first polymerization inhibitor and a first solvent, and heating the mixture to perform an epoxy ring-opening reaction, and purifying the obtained product to obtain a UV active substance; wherein the molar ratio of N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine to acrylic acid is 1:3;

[0022] Step 2: Mixing a plurality of polymerization monomers, an initiator and a second solvent, heating and copolymerizing the mixture to obtain a copolymer containing a carboxyl group, and diluting the mixture with a third solvent; Step 1 and Step 2 may be performed in any order;

[0023] Step 3: Mix the copolymer containing carboxyl group, UV active substance and the second organotin catalyst and heat them to carry out grafting reaction to obtain UV viscosity-reducing adhesive containing acrylate copolymer.

[0024] In some embodiments of the present invention, in step 1, the reaction temperature of the epoxy ring-opening reaction is 55-65° C., the reaction time is 8-12 hours, and the reaction atmosphere is air; the molar ratio of the first organic tin catalyst to N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine is (0.0005-0.002):1; the first polymerization inhibitor is 2,5-di-tert-butylhydroquinone, and the molar ratio of the first polymerization inhibitor to N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine is (0.0005-0.002):1; the first solvent is ethyl acetate, and the molar ratio of the first solvent to N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine is (10-30):1; purification includes volatilizing the first solvent and unreacted reactants.

[0025] In some embodiments of the present invention, in step 2, the reaction temperature of the copolymerization reaction is 60-70° C., the reaction time is 8-12 hours, and the reaction atmosphere is nitrogen; the initiator is azobisisobutyronitrile, and the amount of the initiator is 0.00005-0.0005 times the total mass of the multiple polymerization monomers; the second solvent is at least one of ethyl acetate and toluene, and the amount of the second solvent is 0.8-1.2 times the total mass of the multiple polymerization monomers; the third solvent is ethyl acetate, and the amount of the third solvent is 0.8-1.2 times the total mass of the multiple polymerization monomers; step 2 obtains a liquid including a copolymer containing a carboxyl group, and the solid content of the liquid is 30%-40%.

[0026] In some embodiments of the present invention, in step 3, the copolymer containing carboxyl groups participates in the mixing and grafting reaction in the form of the liquid containing the copolymer containing carboxyl groups obtained in step 2, and the UV active substance and the second organic tin catalyst are sequentially added into the liquid containing the copolymer containing carboxyl groups; the amount of the second organic tin catalyst is 0.00002 to 0.0001 times of the copolymer containing carboxyl groups; a second polymerization inhibitor can also be added in step 3, and the amount of the second polymerization inhibitor is 0.00002 to 0.0001 times of the copolymer containing carboxyl groups; the reaction temperature of the grafting reaction is 55 to 65°C, the reaction time is 8 to 12 hours, and the reaction atmosphere is air.

[0027] To achieve the third purpose of the present invention, the present invention provides a UV viscosity-reducing adhesive composition, characterized in that it includes a UV viscosity-reducing adhesive, a photoinitiator and a thermal curing agent; the UV viscosity-reducing adhesive is a UV viscosity-reducing adhesive described in any of the above schemes; the thermal curing agent contains a group that can react with a hydroxyl group.

[0028] In some embodiments of the present invention, the thermal curing agent is a polyisocyanate compound, the photoinitiator is at least one of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide and 1-hydroxycyclohexyl phenyl ketone, and the mass ratio of the UV viscosity-reducing adhesive, the photoinitiator and the thermal curing agent is (90~105): (0.1~0.6): (0.1~0.4).

[0029] In some embodiments of the present invention, the UV viscosity-reducing adhesive composition is prepared by mixing a UV viscosity-reducing adhesive, a photoinitiator and a thermal curing agent and then heating them for reaction.

[0030] In some embodiments of the present invention, the UV viscosity-reducing adhesive composition further includes a fifth solvent, the fifth solvent is ethyl acetate, and the amount of the fifth solvent is 0 to 1.2 times the total mass of the UV viscosity-reducing adhesive, the photoinitiator and the thermal curing agent.

[0031] To achieve the fourth object of the present invention, the present invention provides a UV anti-viscosity tape, which includes a substrate and a UV anti-viscosity adhesive layer arranged on the substrate, and the UV anti-viscosity adhesive layer is obtained by thermally curing the UV anti-viscosity adhesive composition of any of the above schemes.

[0032] To achieve the fourth object of the present invention, the present invention provides a method for preparing the above-mentioned UV anti-viscosity tape, which comprises the following steps:

[0033] Step A: coating the UV viscosity-reducing adhesive composition on a substrate, wherein the substrate is at least one of a release film, a release paper, a polyester or polyimide film, and a foam;

[0034] Step B: Put the tape obtained in step A into an oven and age it in air at 55-65° C. for 8-12 hours to obtain a UV de-tackifying tape, wherein the thickness of the UV de-stressing tape is 10-60 μm.

[0035] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0036] The side-group multifunctional acrylate UV viscosity-reducing adhesive synthesized by the present invention can have the UV viscosity-reducing function without adding UV viscosity-reducing active monomers or oligomers; the introduction of multi-acrylate functionality is beneficial to enhancing the UV light viscosity-reducing effect and improving the viscosity-reducing efficiency; the UV active substance with multi-acrylate functionality is connected to the side base of the acrylate main adhesive by chemical reaction, which is beneficial to promoting the compatibility of various components in the UV adhesive material and achieving stable performance. The UV viscosity-reducing adhesive composition prepared by the present invention has the characteristics of few types of composition formulas, good compatibility, and simple preparation steps. The UV viscosity-reducing tape finally obtained has high bonding strength before light irradiation, low bonding strength after UV irradiation, good viscosity-reducing effect, and no residual glue after UV irradiation. DETAILED DESCRIPTION

[0037] The embodiments of the present invention provide a UV viscosity-reducing adhesive having a side group containing a multifunctional acrylate group, a UV viscosity-reducing adhesive composition containing the UV viscosity-reducing adhesive, a UV viscosity-reducing adhesive tape prepared from the UV viscosity-reducing adhesive composition, and a preparation method thereof. The UV viscosity-reducing adhesive, the UV viscosity-reducing adhesive composition, and the UV viscosity-reducing adhesive tape of the present embodiment are suitable for the semiconductor industry and the flexible display industry, and can be used in the material preparation and transportation process in the fields of semiconductor chips, transistors, integrated circuits, etc., and can also be used in other scenes requiring bonding and debonding.

[0038] The UV viscosity-reducing adhesive containing multifunctional acrylate groups in the side groups can achieve the effect of viscosity reduction by cross-linking the multifunctional acrylate groups after UV irradiation without adding UV active monomers or oligomers. To this end, the present embodiment provides a UV viscosity-reducing adhesive containing an acrylate copolymer, which includes a main chain and multifunctional acrylate side groups grafted on the main chain. The main chain is formed by copolymerization of a variety of polymerized monomers including acrylate soft monomers, acrylate hard monomers and functional acrylate monomers. The acrylate soft monomer is a long-chain alkyl acrylate, and the number of carbon atoms of the long-chain alkyl is greater than or equal to 4. The acrylate hard monomer is methyl (meth) acrylate, and the functional acrylate monomer is a carboxyl-containing acrylic acid (ester) and a hydroxyl-containing acrylate. The multifunctional acrylate side groups are formed by the reaction of a UV active substance containing multiple acrylate groups and one epoxy group in each molecule with a carboxyl group on the main chain through an epoxy group.

[0039] In some examples, the UV active material is a product having three acrylate groups formed by reacting three epoxy groups in each molecule of N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine with acrylic acid. The UV active material is a multi-acrylate functional epoxy small molecule.

[0040] In some examples, the raw materials required for the preparation of the UV active material include: in molar equivalents, 1.0 equivalent of a tetrafunctional epoxy resin based on m-phenylenediamine (also known as N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine, CAS No.: 63738-22-7, which can be purchased from Tiantai Chemical, brand TT480), 3.0 equivalents of acrylic acid (AA), 0.0005 to 0.002 equivalents, such as 0.001 equivalents of an organic tin catalyst, 0.0005 to 0.002 equivalents, such as 0.001 equivalents of an inhibitor, and 10 to 30 equivalents, such as 20.0 equivalents of an ethyl acetate solvent. The inhibitor can be 2,5-di-tert-butylhydroquinone (BHT). The approximate reaction equation of the above raw materials is as follows.

[0041]

[0042] The solvent ethyl acetate plays the role of dispersing reactants and catalysts, the tetraepoxy-functional TT480 provides epoxy group reaction sites, and the carboxyl groups in acrylic acid will react chemically with the epoxy groups under the action of the organic tin catalyst, so that an average of three epoxy groups in each TT480 molecule are converted into acrylate groups through chemical changes, and the remaining epoxy group is reserved for the subsequent preparation of acrylate copolymers containing multi-functional acrylate groups on the side groups.

[0043] The reaction temperature of the reaction is 55-65°C, for example, 60°C, and the reaction time is 8-12 hours, for example, 10 hours. No nitrogen atmosphere is required, and the reaction is carried out in an air atmosphere to avoid the self-polymerization of the acrylic monomer. After the reaction is completed, the solvent and the unreacted reactants are naturally volatilized to obtain a multi-acrylate functional epoxy small molecule UV active material.

[0044] In some examples, the raw material ratio of the main chain of the acrylate copolymer, i.e., the carboxyl-containing copolymer, is measured in parts by weight, including 70 to 90 parts of acrylate soft monomers, preferably 70 to 80 parts, and the acrylate soft monomers can be, for example, isooctyl acrylate (2-EHA), n-butyl acrylate (BA) or n-hexyl acrylate (HA) or a mixture of one or more thereof; 10 to 30 parts of acrylate hard monomers, preferably 20 to 30 parts, and the acrylate hard monomers can be, for example, methyl methacrylate (MMA), methyl acrylate (MA) or a mixture of one or more thereof; 5 to 15 parts of functional acrylate monomers, preferably 8 to 12 parts, and the functional acrylate monomers can be, for example, acrylic acid (AA) and A mixture of one or two of hydroxyethyl acrylate (2-HEA or HEA) or hydroxybutyl acrylate (4-HBA), etc., the mass ratio of acrylic acid (AA) to hydroxyethyl acrylate (2-HEA) or hydroxybutyl acrylate (4-HBA) can be 1: (0.2-1), preferably 1: (0.2-0.5); the amount of the initiator is 0.00005-0.0005 times the total amount of the above monomers, for example, it can be 0.01-0.05 parts, and the initiator can be azobisisobutyronitrile (AIBN); the amount of the solvent is 0.8-1.2 times the total mass of the above monomers, for example, it can be 100-120 parts, and the solvent can be a mixture of one or more of ethyl acetate, toluene, etc.

[0045] Among them, the main function of the soft monomer and the hard monomer is to adjust the glass transition temperature of the adhesive so that it can adapt to specific application requirements (generally speaking, its glass transition temperature is between -20°C and -50°C), and its secondary function is to increase the interfacial wetting performance of the adhesive; the main function of acrylic acid is to serve as a reaction site for subsequent epoxy small molecules with multi-acrylate functionality, and its secondary function is to coordinate the soft and hard monomers to regulate the glass transition temperature of the adhesive and improve the bonding and adhesion performance; the main function of hydroxyethyl acrylate or hydroxybutyl acrylate is to provide thermal curing reaction sites with curing agents such as polyisocyanate compounds, so that the adhesive can complete the thermal crosslinking process, and its secondary function is to increase the interfacial polarity and improve the bonding performance.

[0046] The reaction conditions for preparing the carboxyl-containing copolymer are, under nitrogen atmosphere, 60-70° C., for example, 65° C., for 8-12 hours, for example, 10 hours. After the reaction is completed, ethyl acetate is added as a diluent, and the amount of the diluent is 0.8-1.2 times the total amount of the above-mentioned monomers, for example, 100 parts. The liquid including the carboxyl-containing copolymer and the solvent (or diluent) obtained in the above steps can be directly used for the next step of reaction, and there is no need to separate and purify the random copolymer. In the liquid, the solid content, i.e., the content of the carboxyl-containing copolymer is 30%-40%. The carboxyl-containing copolymer can be a random copolymer.

[0047] As a specific example, the comonomers are isooctyl acrylate (2-EHA), methyl acrylate (MA), acrylic acid (AA) and hydroxyethyl acrylate (HEA), and the approximate reaction equation is as follows.

[0048]

[0049] Wherein m, n, o, and p reflect the feed ratio, and the prepared copolymer is a random copolymer.

[0050] The UV active substance and the carboxyl-containing copolymer may be prepared in any order, for example, the UV active substance may be prepared first, or the carboxyl-containing copolymer may be prepared first, or the UV active substance and the carboxyl-containing copolymer may be prepared simultaneously.

[0051] In some examples, the UV active substance and the carboxyl-containing copolymer are reacted, and the epoxy group of the UV active substance reacts with the carboxyl group of the carboxyl-containing copolymer to obtain an acrylate copolymer grafted with multifunctional acrylate side groups on the main chain. The raw material ratio for preparing the acrylate copolymer includes, by weight: 20 to 40 parts of the carboxyl-containing copolymer, preferably 30 to 40 parts, which is used in the form of a liquid including carboxyl-containing acrylate and solvent prepared in the previous step, and the amount of the liquid can be 75 to 100 parts; 2 to 5 parts of the UV active substance, i.e., epoxy small molecules with multi-acrylate functionality; the amount of the organic tin catalyst is 0.00002 to 0.0001 times the amount of the carboxyl-containing copolymer, for example, it can be 0.001 to 0.002 parts. The raw material can also contain an inhibitor, and the amount of the inhibitor is 0.00002 to 0.0001 times the amount of the carboxyl-containing copolymer, for example, it can be 0.001 to 0.002 parts.

[0052] The copolymer containing carboxyl groups provides carboxyl reaction sites, which react with the epoxy small molecules with multi-acrylate functionality of UV active substances under the action of organic tin catalysts. The approximate reaction equation is shown below.

[0053]

[0054] R1 is a long-chain alkyl side group of the acrylic acid ester soft monomer, for example, it can be isooctyl; R2 is a side group of the acrylic acid ester hard monomer, here is methyl; R3 and R4 are functional monomer side groups, R3 can be, for example, 2-hydroxyethyl, here R4 is H, and -COOR4 in the structural formula is a carboxyl group.

[0055] The reaction conditions are as follows: a UV active substance, i.e., a multi-acrylate functional epoxy small molecule and an organic tin catalyst are sequentially added to a liquid of an acrylate containing a carboxyl group, the reaction temperature is 55 to 65°C, for example, 60°C, the reaction time is 8 to 12 hours, for example, 10 hours, and no nitrogen atmosphere is required. The reaction is carried out in an air atmosphere to avoid self-polymerization of the acrylic monomer. After the reaction is completed, a UV viscosity-reducing adhesive containing the acrylate copolymer is prepared. The UV viscosity-reducing adhesive may also contain at least one of a solvent / diluent, such as toluene and ethyl acetate. The acrylate copolymer prepared by the above steps can obtain a UV viscosity-reducing adhesive without removing the solvent / diluent, and can be used directly in subsequent steps as the main adhesive of the tape. The mass proportion of the acrylate copolymer in the UV viscosity-reducing adhesive, i.e., the solid content of the UV viscosity-reducing adhesive, may be 30% to 50%. In other examples, the acrylate copolymer may also be separated from the solvent and used as a UV viscosity-reducing adhesive.

[0056] In some examples, the present embodiment also provides a UV viscosity-reducing adhesive composition comprising the above-mentioned UV viscosity-reducing adhesive, which, in addition to the above-mentioned UV viscosity-reducing adhesive, also contains a photoinitiator and a thermal curing agent. Among them, the photoinitiator is diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide and / or 1-hydroxycyclohexyl phenyl ketone, which plays a role in initiating the polymerization of multifunctional acrylate groups. Since the multifunctional acrylate groups are on the side groups of the adhesive molecules, the crosslinking density of the adhesive will be greatly increased when polymerization occurs. The photoinitiator is used to make the acrylate copolymer containing multifunctional acrylate groups on the side groups under UV light quickly crosslink and thus play a viscosity-reducing effect; the curing agent is a polyisocyanate compound such as diisocyanate, which plays a thermal crosslinking role, so that the UV viscosity-reducing adhesive composition has the effect of bonding strength and sustained adhesion.

[0057] In some examples, the composition comprises, by weight, 90 to 105 parts, such as 90 to 98 parts, of a UV viscosity-reducing adhesive, 0.1 to 0.6 parts of a photoinitiator, and 0.1 to 0.4 parts of a thermal curing agent.

[0058] In some examples, the composition may or may not include a solvent, such as ethyl acetate, which serves to disperse the adhesive, initiator and curing agent. The amount of the solvent is 0 to 1.2 times the total mass of the UV viscosity-reducing adhesive, the photoinitiator and the thermal curing agent, such as 0 to 120 parts, such as 60 to 120 parts.

[0059] In some examples, the method for preparing a UV viscosity-reducing adhesive composition includes uniformly mixing a UV viscosity-reducing adhesive, a photoinitiator, and a thermal curing agent. After uniform mixing, the UV viscosity-reducing adhesive composition may be partially thermally cured to adjust the crosslinking degree and viscosity of the UV viscosity-reducing adhesive composition.

[0060] In some examples, the present embodiment further provides a UV de-viscosity tape, which includes a substrate and a UV de-viscosity adhesive layer disposed on the substrate, wherein the UV de-viscosity adhesive layer is obtained by curing the above-mentioned UV de-viscosity adhesive composition, i.e., thermally curing. The substrate may be at least one of a release film, a release paper, a polyester or polyimide film, and a foam. The thickness of the UV de-viscosity tape may be 10 to 60 μm.

[0061] In some examples, the preparation steps of the UV anti-viscosity tape include: after preparing the UV anti-viscosity adhesive composition, coating the UV anti-viscosity adhesive composition on a substrate, and then placing the UV anti-viscosity adhesive composition in an oven at 55 to 65°C, such as 60°C, for aging for 8 to 12 hours, such as 10 hours, to prepare the UV adhesive tape. The purpose of aging is to remove at least part of the solvent and promote the thermal curing and crosslinking of the UV anti-viscosity tape. Since this process is carried out in the air, the oxygen in the air has an inhibitory effect, so this process does not cause the side-group multifunctional acrylate in the UV anti-viscosity tape to undergo polymerization. After aging is completed, the UV anti-viscosity tape is prepared.

[0062] The present invention will be further described in detail by way of specific examples. The substances with the same names in the following examples and comparative examples have the same types and sources.

[0063] Examples 1 to 8

[0064] The UV viscosity-reducing adhesives, UV viscosity-reducing adhesive compositions, and adhesive tapes of Examples 1 to 8 are mainly prepared by the following steps:

[0065] Step 1: Synthesis of UV active material (3AA-T).

[0066] 1.0 equivalent of a tetrafunctional epoxy resin based on m-phenylenediamine (Tiantai Chemical, brand TT480), 3.0 equivalent of acrylic acid, 0.01 equivalent of an organic tin catalyst, 0.001 equivalent of a 2,5-di-tert-butylhydroquinone (BHT) inhibitor, and 20.0 equivalent of an ethyl acetate solvent were added to the reactor in sequence. The reaction temperature of the reaction was 60°C, the reaction time was 10 hours, and no nitrogen atmosphere was required. The reaction was carried out in an air atmosphere to avoid the self-polymerization of the acrylic monomer. After the reaction was completed, the solvent and the unreacted reactants were naturally volatilized to obtain a multi-acrylate functional epoxy small molecule, i.e., a UV active substance.

[0067] Step 2: Synthesis of copolymers containing carboxyl groups.

[0068] Prepare reactants: 110 parts of polymerization monomers, prepared according to the feed ratio in Table 1, in which the soft acrylate monomer is isooctyl acrylate (2-EHA), the hard acrylate monomer is methyl acrylate (MA), and the functional acrylate monomer is a mixture of acrylic acid (AA) and hydroxyethyl acrylate (HEA); 0.01 parts of initiator azobisisobutyronitrile (AIBN); and 100 parts of a mixture of solvent ethyl acetate and toluene.

[0069] The reaction conditions are: 65°C for 10 hours under nitrogen atmosphere; after the reaction, 100 parts of ethyl acetate are added as a diluent. A liquid including a copolymer containing a carboxyl group and a solution (diluent) is obtained. Information of the obtained product is shown in Table 1 below.

[0070] Table 1 Monomer feed ratio and product information.

[0071]

[0072] Step 3: Prepare UV viscosity-reducing adhesive by chemical grafting method.

[0073] According to the types and amounts of raw materials of each embodiment in Table 2, 100 parts of the liquid of the copolymer containing carboxyl prepared in the previous step of Preparation Example 1 or 2, different amounts of epoxy small molecules with multi-acrylate functionality (3AA-T), 0.001 parts of organic tin catalyst, and 0.001 parts of polymerization inhibitor were weighed. The reaction conditions are as follows: the epoxy small molecules with multi-acrylate functionality (3AA-T), the organic tin catalyst, and the polymerization inhibitor are sequentially added to the liquid of the copolymer containing carboxyl, the reaction temperature is 60°C, the reaction time is 10 hours, and no nitrogen atmosphere is required. After the reaction is completed, a UV viscosity-reducing adhesive (acrylate main glue) is prepared.

[0074] Step 4: preparing a UV viscosity-reducing adhesive composition.

[0075] According to the amount of raw materials in each example in Table 2, weigh the photoinitiator and the thermal curing agent, add them to the UV viscosity-reducing adhesive (acrylate main adhesive) prepared in the above step 3, stir for 20 minutes under nitrogen atmosphere at room temperature, and finally keep the temperature at 65°C under nitrogen atmosphere for reaction for 10 hours.

[0076] Step 5: Prepare UV tape.

[0077] The UV viscosity-reducing adhesive composition obtained in step 4 is coated on the release film, and the release film is placed in a 60° C. oven for aging for 10 hours; after aging, a 50 μm thick PET plastic film is coated on the other side of the tape, and finally a UV viscosity-reducing tape with a thickness of about 50 μm is prepared, which is a UV viscosity-reducing single-sided tape.

[0078] Table 2 Types and amounts of raw materials used in each example

[0079]

[0080] In order to demonstrate the effect of chemical grafting of multifunctional acrylate groups to the main chain, a UV viscosity-reducing adhesive composition of a multifunctional acrylate-based UV active substance and a carboxyl-containing copolymer was prepared by a physical mixing method. The specific preparation method is as follows.

[0081] Comparative Example 1

[0082] 100 parts of Preparation Example 1, 2 parts of 3AA-T, 0.1 parts of thermal curing agent and 0.1 parts of photoinitiator were added to the reactor in sequence, and stirred for 20 minutes under nitrogen atmosphere at room temperature, and then heated to 65°C under nitrogen atmosphere for reaction for 10 hours to obtain the UV viscosity-reducing adhesive composition of Comparative Example 1. The UV viscosity-reducing adhesive composition was then coated on a release film, which was placed in a 60°C oven for aging for 10 hours; after aging, a 50 μm thick PET plastic film was coated on the other side of the tape, and finally a UV viscosity-reducing single-sided tape with a thickness of about 50 μm was prepared.

[0083] Since no organic tin catalyst is added in this comparative example, 3AA-T is not effectively grafted onto the acrylate main adhesive through chemical reaction. At this time, the UV active substance 3AA-T and the acrylate main adhesive are in a physical state.

[0084] Comparative Example 2

[0085] All preparation steps were the same as those in Comparative Example 1, but the amount of 3AA-T used was changed from 2 parts in Comparative Example 1 to 5 parts.

[0086] Table 3 Types and amounts of raw materials for comparative examples 1 and 2

[0087]

[0088] In order to reflect the role of the multifunctional acrylate group in the side group of the UV viscosity-reducing adhesive, a UV viscosity-reducing adhesive containing a monofunctional acrylate group based on glycidyl methacrylate (GMA) was prepared by chemical grafting. The specific preparation method is as follows.

[0089] Comparative Example 3

[0090] First, 100 parts of Preparation Example 1, 2 parts of GMA, 0.001 parts of organic tin catalyst and 0.001 parts of inhibitor were added to the reactor in sequence. The reaction conditions are reaction temperature 60°C, reaction time 10 hours, and no nitrogen atmosphere is required. Then, 0.1 parts of thermal curing agent and 0.1 parts of photoinitiator were added and stirred for 20 minutes under nitrogen atmosphere at room temperature, and finally the temperature was raised to 65°C under nitrogen atmosphere for 10 hours to obtain a UV viscosity-reducing adhesive composition containing multifunctional acrylate groups in the side groups. The viscosity-reducing adhesive composition was then coated on the release film and placed in a 60°C oven for aging for 10 hours; after aging, a 50 μm thick PET plastic film was covered on the other side of the tape, and finally a UV viscosity-reducing single-sided tape with a thickness of about 50 μm was prepared.

[0091] Comparative Example 4

[0092] All preparation steps were the same as those in Comparative Example 3, but the amount of GMA was changed from 2 parts in Comparative Example 3 to 5 parts.

[0093] Table 4 Types and amounts of raw materials for comparative examples 3 and 4

[0094]

[0095] The following performance tests were performed on all the adhesive tape samples of the embodiments and comparative examples.

[0096] Taking a UV anti-viscosity tape with a thickness of 50 μm on a PET substrate as an example, the preparation description and subsequent performance tests are carried out. The UV anti-viscosity adhesive composition prepared in the above embodiments and comparative examples is coated on a polyethylene terephthalate (PET) plastic substrate with a thickness of 150 μm. The coating thickness is set according to the solid content of each embodiment sample, and the coating thickness is roughly in the range of 250 to 300 μm; then it is placed in a 60°C oven for 10 hours to remove the solvent and mature the UV anti-viscosity adhesive; finally, a UV anti-viscosity tape with a thickness of about 50 μm is obtained. The matured UV anti-viscosity tape is cut into 25 mm wide and attached to a SUS304 steel plate for 180° peel strength and adhesion performance tests.

[0097] The 180° peel strength test refers to GB / T2792-1998 standard, with a peel rate of 300mm / min, and is tested at room temperature and pressure. For samples before UV irradiation, normal testing is sufficient; for samples after UV irradiation, UV light is used for 30s, and the received UV dose is 1500mJ / cm 2 Then, test again. After the test is completed, observe the residual glue on the peeling interface.

[0098] The adhesive performance refers to GB / T 4851 2014 standard, the ambient temperature is 25°C, the weight is 1kg, and the displacement (mm) of the UV anti-adhesion film after 4 hours of bonding is tested.

[0099] The test results of peel force, residual adhesive and holding performance are shown in Table 5 below.

[0100] Table 5 Performance test results of embodiments and comparative examples

[0101]

[0102]

[0103] For the samples of Examples 1 to 4, before UV irradiation, the peel strength was between 6 and 11 N / 25 mm, and there was no residual glue phenomenon, and at the same time, it had good adhesion performance. The reason for the difference in peel strength is the different contents of 3AA-T and curing agent. The higher the 3AA-T content, the higher the peel strength, and the higher the curing agent content, the lower the peel strength. The introduction of 3AA-T produces hydroxyl groups that increase the interface polarity and promote adhesion, while the introduction of the curing agent increases the cross-linking density, which is not conducive to interface adhesion. After UV irradiation, the peel strength of the samples of Examples 1-4 is significantly reduced, and the effect is obvious with the increase of 3AA-T content. At the same time, no residual glue appears on the adherend.

[0104] Compared with Examples 1 to 4, the samples of Examples 5 to 8 have more soft monomer (2-EHA) added. Before UV irradiation, when the curing agent content is low (Examples 5 to 6), the adhesive failure is mixed failure, there is residual glue, and the adhesive holding performance is also poor; after the curing agent content is increased, although there is no residual glue and the adhesive holding performance is good, the peel strength decreases significantly. After UV irradiation, the peel strength of the samples of Examples 5 to 8 is also significantly reduced, and there is no residual glue on the steel plate during debonding.

[0105] The samples of Comparative Examples 1 and 2 are samples of UV active substances blended with acrylate main glue. After UV irradiation, they can still play a viscosity-reducing role, but the effect is obviously not as good as the samples prepared by chemical grafting method with the same composition formula (Example 1 and Example 2).

[0106] The samples of Comparative Examples 3 and 4 are UV viscosity-reducing adhesives containing monofunctional acrylate groups. Their UV viscosity-reducing effects are inferior to those of multifunctional acrylate-based UV viscosity-reducing adhesives (Examples 1 and 2) with the same formula and preparation method.

[0107] The results of Comparative Examples 1 to 4 show that the UV viscosity-reducing adhesive prepared by the method of chemical reaction-based grafting of multifunctional acrylates in the present invention has better effects than the method of physical blending and monofunctional grafting.

[0108] In summary, 3AA-T is introduced into the carboxyl-containing acrylate copolymer by chemical grafting, which promotes the bonding strength before UV irradiation and gives the function of reducing viscosity by UV irradiation. Combining the 8 examples, it can be known that the best comprehensive performance is Example 2, and the final bonding strength before UV irradiation is 10.26N / 25mm, the bonding strength after UV irradiation is 0.08N / 25mm, the viscosity reduction effect is 99.2%, and there is no residual glue throughout the process.

[0109] Finally, it should be emphasized that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A UV viscosity-reducing adhesive, characterized in that The acrylate copolymer comprises a main chain and multifunctional acrylate side groups grafted on the main chain; The main chain is formed by copolymerization of multiple polymerized monomers including soft acrylate monomers, hard acrylate monomers and functional acrylate monomers; the soft acrylate monomer is a long-chain alkyl acrylate, and the number of carbon atoms of the long-chain alkyl is greater than or equal to 4; the hard acrylate monomer is methyl (meth)acrylate; and the functional acrylate monomer is a carboxyl-containing acrylic acid (ester) and a hydroxyl-containing acrylic acid ester; The multifunctional acrylate side groups are formed by a UV-active substance containing multiple acrylate groups and one epoxy group in each molecule through the reaction of the epoxy group with the carboxyl group on the main chain.

2. A UV viscosity-reducing adhesive according to claim 1, characterized in that The UV active substance is a product having three acrylate groups in each molecule of N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine reacted with acrylic acid.

3. A UV viscosity-reducing adhesive according to claim 1 or 2, characterized in that The mass ratio of the acrylate soft monomer, the acrylate hard monomer and the functional acrylate monomer is (70-90): (10-30): (5-15); preferably, the mass ratio of the acrylate soft monomer, the acrylate hard monomer and the functional acrylate monomer is (70-80): (20-30): (8-12); The mass ratio of the carboxyl-containing acrylic acid (ester) to the hydroxyl-containing acrylic acid ester is 1: (0.2-1); preferably, the mass ratio of the carboxyl-containing acrylic acid (ester) to the hydroxyl-containing acrylic acid ester is 1: (0.2-0.5); The mass ratio of the UV active substance to the total mass of the plurality of polymerizable monomers is (2-5):(20-40); preferably, the mass ratio of the UV active substance to the total mass of the plurality of polymerizable monomers is (2-5):(30-40).

4. A UV viscosity-reducing adhesive according to claim 1 or 2, characterized in that The acrylic acid ester soft monomer is at least one of isooctyl acrylate, n-butyl acrylate, and n-hexyl acrylate; the acrylic acid ester hard monomer is at least one of methyl methacrylate and methyl acrylate; the carboxyl-containing acrylic acid (ester) is acrylic acid; the hydroxyl-containing acrylic acid is at least one of hydroxyethyl acrylate and hydroxybutyl acrylate; And / or, the UV viscosity-reducing adhesive further includes a solvent, the mass proportion of the acrylate copolymer in the acrylate copolymer and the solvent is 30% to 50%, and the solvent is at least one of ethyl acetate and toluene.

5. The method for preparing a UV viscosity-reducing adhesive according to any one of claims 1 to 4, characterized in that The following steps are involved: Step 1: mixing N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine, acrylic acid, a first organic tin catalyst, a first polymerization inhibitor and a first solvent, and heating the mixture to perform an epoxy ring-opening reaction, and purifying the obtained product to obtain a UV active substance; wherein the molar ratio of N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine to acrylic acid is 1:3; Step 2: Mix the plurality of polymerization monomers, the initiator and the second solvent, heat and copolymerize them to obtain a copolymer containing a carboxyl group, and dilute it with a third solvent; Step 1 and Step 2 can be performed in any order; Step 3: Mix the copolymer containing carboxyl groups, the UV active substance and the second organotin catalyst, and heat them to carry out a grafting reaction to obtain a UV viscosity-reducing adhesive containing the acrylate copolymer.

6. The preparation method according to claim 5, characterized in that In the step 1, the reaction temperature of the epoxy ring-opening reaction is 55-65° C., the reaction time is 8-12 hours, and the reaction atmosphere is air; the molar ratio of the first organic tin catalyst to the N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine is (0.0005-0.002):1; the first polymerization inhibitor is 2,5-di-tert-butylhydroquinone, and the molar ratio of the first polymerization inhibitor to the N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine is (0.0005-0.002):1; the first solvent is ethyl acetate, and the molar ratio of the first solvent to the N,N,N',N'-tetra(oxiranylmethyl)-1,3-phenylenediamine is (10-30):1; the purification includes volatilizing the first solvent and unreacted reactants; In the step 2, the reaction temperature of the copolymerization reaction is 60-70° C., the reaction time is 8-12 hours, and the reaction atmosphere is nitrogen; the initiator is azobisisobutyronitrile, and the amount of the initiator is 0.00005-0.0005 times the total mass of the multiple polymerization monomers; the second solvent is at least one of ethyl acetate and toluene, and the amount of the second solvent is 0.8-1.2 times the total mass of the multiple polymerization monomers; the third solvent is ethyl acetate, and the amount of the third solvent is 0.8-1.2 times the total mass of the multiple polymerization monomers; the step 2 obtains a liquid including the copolymer containing a carboxyl group, and the solid content of the liquid is 30%-40%; In the step 3, the copolymer containing carboxyl groups participates in the mixing and grafting reaction in the form of the liquid containing the copolymer containing carboxyl groups obtained in step 2, and the UV active substance and the second organic tin catalyst are sequentially added into the liquid containing the copolymer containing carboxyl groups; the amount of the second organic tin catalyst is 0.00002 to 0.0001 times of the copolymer containing carboxyl groups; a second polymerization inhibitor can also be added in the step 3, and the amount of the second polymerization inhibitor is 0.00002 to 0.0001 times of the copolymer containing carboxyl groups; the reaction temperature of the grafting reaction is 55 to 65° C., the reaction time is 8 to 12 hours, and the reaction atmosphere is air.

7. A UV viscosity-reducing adhesive composition, characterized in that It comprises a UV viscosity-reducing adhesive, a photoinitiator and a thermal curing agent; the UV viscosity-reducing adhesive is a UV viscosity-reducing adhesive according to any one of claims 1 to 4 or a UV viscosity-reducing adhesive obtained by the preparation method according to claim 5 or 6; the thermal curing agent contains a group that can react with a hydroxyl group.

8. A UV viscosity reducing adhesive composition according to claim 7, characterized in that The thermal curing agent is a polyisocyanate compound, the photoinitiator is at least one of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide and 1-hydroxycyclohexyl phenyl ketone, and the mass ratio of the UV viscosity-reducing adhesive, the photoinitiator and the thermal curing agent is (90-105): (0.1-0.6): (0.1-0.4); And / or, the UV viscosity-reducing adhesive composition is prepared by mixing a UV viscosity-reducing adhesive, a photoinitiator and a thermal curing agent and then heating them for reaction; And / or, the UV viscosity-reducing adhesive composition further includes or does not include a fifth solvent, the fifth solvent is ethyl acetate, and the amount of the fifth solvent is 0 to 1.2 times the total mass of the UV viscosity-reducing adhesive, the photoinitiator and the thermal curing agent.

9. A UV adhesive tape, characterized in that The invention comprises a substrate and a UV viscosity-reducing adhesive layer arranged on the substrate, wherein the UV viscosity-reducing adhesive layer is obtained by ripening the UV viscosity-reducing adhesive composition according to claim 7 or 8.

10. The method for preparing a UV adhesive tape according to claim 9, characterized in that The following steps are involved: Step A: coating the UV viscosity-reducing adhesive composition onto the substrate, wherein the substrate is at least one of a release film, a release paper, a polyester or polyimide film, and a foam; Step B: placing the tape obtained in step A into an oven and aging it in air at 55-65° C. for 8-12 hours to obtain a UV de-tackifying tape, wherein the thickness of the UV de-stressing tape is 10-60 μm.

Citation Information

Patent Citations

  • UV viscosity-reducing adhesive liquid, single-sided UV viscosity-reducing protective film and preparation method thereof

    CN113897168B

  • Two-component high-temperature-resistant UV viscosity-reducing adhesive as well as preparation method and application thereof

    CN116262873A

  • UV (ultraviolet) viscosity-reducing adhesive as well as preparation method and application thereof

    CN118496783A

  • Polyurethane type UV viscosity-reducing adhesive based on dimer acid and preparation method of polyurethane type UV viscosity-reducing adhesive

    CN118652657A

Cited By

  • UV viscosity-reducing adhesive with interpenetrating network structure, viscosity-reducing adhesive film and viscosity-reducing adhesive tape

    CN121319822A

  • Quick-response UV visbreaking type OCA adhesive, preparation method thereof and adhesive film

    CN121518067A